NEW CT CRITERIA FOR PREDICTING SURGICAL TREATMENT IN PATIENTS WITH DEVELOPMENTAL MALFORMATIONS OF THE EXTERNAL AUDITORY CANAL (Medical science of Uzbekistan, 2024)
In order to classify patients with ear malformations and treat them effectively, accurate knowledge and a uniform description of defects are necessary.A complete study. Clinical and audiometric research methods can be used, as well as X-ray methods. An accurate anatomical description of malformations using imaging procedures is necessary, especially with regard to the planning and results of surgical reconstructions of the outer and middle ear.Research materials and methods. We analyzed the Jahrsdoerfer criteria, the new/modified anatomical points considered in our study, as well as the angle of the anvil-stapes joint. The following are specific anatomical criteria and corresponding points awarded when evaluating computed tomography of the temporal bones in congenital stenosis and atresia of the external auditory canal.Results. TMJ is a safe surgical limit for channeloplasty; therefore, group I patients will have much more operating space than group II patients. Considering the above, that the position of the facial nerve was not statistically significant (P>0.05) between group I and group II, we assume that the displacement of the TMJ back contributed more to a decrease in the diameter of the medial canal.Conclusions. We have identified new/modified anatomical features that are often found in CT scans in a large group of patients from groups I and II. A review of surgical data shows that a large MHC obstruction makes it difficult to examine the stirrup and anvil-stapes joint, as well as assess integrity and mobility, and thus increases the complexity of atresioplasty.